The typology of Muhammadiyah Sufism: tracing its figures’ thoughts and exemplary lives - Biyanto Biyanto (Indonesian Journal of Islam and Muslim Societies, 2017)
; " This article explores the style of sufism from the perspective of Muhammadiyah.It is a literature study on the official fatwa given by Muhammadiyah on sufism as a part of spiritual dimension in Islamic teaching. This study places a number of Muhammadiyah figures as the subject of study. This study concludes that the views of Muhammadiyah and its figures on sufism are very positive. Sufistic life in fact also becomes a trend among the followers of Muhammadiyah. Important styles of Muhammadiyah sufism include: first, Muhammadiyah sufistic teachings are based on pure monotheism. The second, Muhammadiyah sufistic is practiced under the frame of shari‘ah, on the basis of the Qur’an and Hadith. Third, the substance of sufism in the Muhammadiyah perspective is noble character that should be realized in daily life. Fourth, the orientation of Muhammadiyah sufism emphasizes the dimension of righteous deeds, social praxis, and of moving from theory to practice. Fifth, Muhammadiyah sufism presents sufistic teachings adjusted to the spirit of modernity so that it may be called modern sufism. Sixth, Muhammadiyah sufism is expressed in more active and dynamic styles. A sufi is not allowed to do nothing, but is obliged to work actively and to interact with society. Seventh, Muhammadiyah sufism stays away from the philosophical sufism discourse that may potentially cause debates. Muhammadiyah views that to become sufi, one should not become the member of sufi order with the style of “teacher-centered” in practice.Artikel ini membahas corak sufisme dalam perspektif Muhammadiyah. Kajianini merupakan studi literatur terhadap fatwa resmi Muhammadiyah terhadap sufisme sebagai bagian dari dimensi spiritual ajaran Islam. Kajian ini juga menempatkan sejumlah tokoh Muhammadiyah sebagai subjek studi. Kajian ini menyimpulkan bahwa perspektif Muhammadiyah dan tokoh-tokohnya terhadap sufisme sangat positif. Kehidupan sufistik dalam kenyataannya juga menjadi trend di kalangan pengikut Muhammadiyah. Corak sufisme Muhammadiyah yang penting meliputi: pertama, ajaran sufisme Muhammadiyah berbasis pada tauhid murni. Kedua, sufisme Muhammadiyah dipraktekkan dalam bingkai syariah, berdasar al-Qur’an dan hadits. Ketiga, substansi sufisme dalam perspektif Muhammadiyah adalah akhlak mulia dan harus diwujudkan dalam kehidupan sehari-hari. Keempat, orientasi sufisme Muhammadiyah menekankan dimensi amal salih, praksis sosial, dan bergerak dari teori ke praktek. Kelima, sufisme Muhammadiyah menampilkan ajaran tasawuf yang disesuaikan dengan spirit modernitas sehingga layak disebut tasawuf modern. Keenam, sufisme Muhammadiyah diekspresikan dalam corak yang lebih aktif dan dinamis. Seorang sufi tidak boleh berpangku tangan, melainkan harus aktifbekerja dan berinteraksi dengan masyarakat. Ketujuh, sufisme Muhammadiyahmenjauhi wacana tasawuf falsafi yang potensial mengundang perdebatan.Terakhir, Muhammadiyah berpandangan untuk menjadi sufi, seseorang tidakharus menjadi anggota tarekat yang dalam prakteknya bercorak guru sentris.